2021
DOI: 10.1097/gox.0000000000003585
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Abdominal Wall Neuromas

Abstract: Background: Neuromas are an under-recognized contributor to chronic abdominal pain. Other than after mesh inguinal hernia repair, surgical management of painful abdominal wall neuromas has not been well established in the literature. Methods: All patients who underwent surgical treatment for painful abdominal wall neuromas by the senior author at Northwestern Memorial Hospital were reviewed. Patients were treated with neuroma excision and allograft nerve reconstruction and/or with targeted muscle reinnervation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…While short-term pain typically requires a hospitalization, long-term pain has not been an issue for these patients, though one patient required physical therapy at 6 months. If chronic pain were to develop, treatment would involve intercostal nerve excision and allograft reconstruction [19]. This has not been necessary to date.…”
Section: Discussionmentioning
confidence: 99%
“…While short-term pain typically requires a hospitalization, long-term pain has not been an issue for these patients, though one patient required physical therapy at 6 months. If chronic pain were to develop, treatment would involve intercostal nerve excision and allograft reconstruction [19]. This has not been necessary to date.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroma-related pain may limit activities of daily living in this population, delaying a return to baseline functioning or employment. 9,19 In prior studies, Park et al reported a 25% prevalence of persistent neuropathic pain following sarcoma surgery with attributed factors of multiple resections and pelvic tumor location; however, neuromas and major nerve injuries were excluded from this cohort. 20 Fiore et al reported a 41% prevalence of neuropathic pain following multivisceral resection for retroperitoneal sarcoma.…”
Section: Background and Rationalementioning
confidence: 99%
“…3,4 Painful neuromas have also been reported following elective hand surgery, 5,6 cosmetic operations, 7 and various others. [8][9][10][11][12] Factors previously associated with painful neuroma development in these populations include involvement of cutaneous nerves 13 and avulsion injury. 14 Sarcomas are malignancies that arise from mesenchymal tissue and most commonly develop in skin, bone, subcutaneous tissue, and muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 73 The last decade has seen a marked expansion in utilization of TMR and RPNI. TMR has expanded to other surgeries, including breast, 74 abdominal wall, 75 and headache surgery. 76 Likewise, studies have shown RPNI can treat symptomatic neuromas in amputee patients.…”
Section: Surgical Treatment Options For Neuropathic Painmentioning
confidence: 99%